Tinjauan Yuridis Partisipasi Masyarakat dalam Proses Pembentukan Undang-Undang - Kamarudin (Perspektif Hukum, 2015)
In the post New-Order era, legislative function given to Indonesian House of Representatives seems more obvious after an Act Number 12 of 2011 juncto Act Number 10 of 2004 on Regulations Making has covered that public has the right to participate in law-making processes. Enactive regulations open opportunity for public to participate in a statute-making processes. Nevertheless, the given opportunity of participation is procedurally still limited and not in full and meaningful participation level. Existing public participation only covers consultation, not a real participation. Public should be able to participate in decision-making processes. Meanwhile, public participation level is substantially still depended on Parliament Members’ spirit of publicness to accommodate public aspiration and to put it on as a norm of statute.